Comparison for color change between benzodifuranone and benzodipyrrolidone based epoxy coating. (April 2020) - Zhang, Haichang; Zeng, Weixiu; Du, Huiling; Ma, Yiting; Ji, Zhuoting; Deng, Zhifeng; Zhou, Qixin
Abstract: Compared to traditional coatings, chromogenic coatings—the color change responds to external environment stimulus—have received lots of attention and being widely explored for applications. Due to their advanced features, the development of promising chromogenic coating systems is highly needed. In this work, a systematical and comprehensive comparison was studied regarding the benzodifuranone and benzodipyrrolidone based epoxy coating with different curing agents. The color change of the coatings was investigated and quantified by using a spectrophotometer and the reason for the color change was understood by UV/Vis characterization. The introduced pigment can react with the amide units of the curing agent to form hydrogen-bonded (NH⋯O) mediates, which leads to chromogenic coatings. The more free NH units (primaquine groups and secondary ammonia units) are contained in the curing agent, the color change is easier and stronger. This work provides a new approach to design chromogenic coatings through forming a hydrogen bonding between a pigment and a curing agent in the coating. Graphical abstract: A systematical and comprehensive comparison was studied regarding the benzodifuranone (BDF) and benzodipyrrolidone (BDP) based epoxy coating with different curing agents. Chromogenic coatings could be obtained through forming a hydrogen bonding between a pigment and a curing agent in the coating. Image 1 Highlights: Comparison was studied between BDF and BDP based epoxy coating with curing agents. Curing agent reacts with BDF to form hydrogen bonding leading to chromogenic coating. A new approach is developed to design chromogenic coating.